Information design aspects of a semiotic software - Pauluk, Marcel Pereira; Battaiola, André Luiz (InfoDesign, 2005)
SignType – Assisted Semiotic Typifier for Phenomenological Data – is a simultaneously didactic and applicable software. Its mains goals are: (1) scientific capacitation of researchers and scholars from various knowledge areas on the methodology of Peircean semiotic classification; and (2) transformation of phenomenological input (impressionistic descriptions) into semiotic output (kinds of sign), optimizing the use of the scientific potential of semiotics by the user. Part of the work carried on this optimization comes from the information design project developed for this application. In this paper, graphic models that aims to represent concepts and other theoretical aspects of Charles S. Peirce’s semiotics are analysed. Their key characteristics are customizability (permits certain information to be seen or not under diverse hierarchy criteria), alterability (being interchangeable for other models) and modularization (making comparisons between ongoing classifications easier).